Prevalence and Pattern of Maxillary Wisdom Tooth Impaction and Angulation in Relation to the Maxillary Sinus among Yemeni Students (Research, Society and Development, 2022)
The goal of this study was to determine the prevalence of maxillary third molar impaction and angulation, as well as its relationship to the maxillary sinus, in a group of Yemeni students. Panoramic x-rays were used to assess 200 students, 102 men and 98 females, in this retrospective investigation. Chi-square tests were used to assess age, gender, maxillary sinus approximation to maxillary third molar roots, depth of impaction, and angulation. A total of 327 maxillary third molars were examined; the most congenitally missing maxillary third molar was on the right side, and females (10.25%) had more maxillary third molars engaged in the maxillary sinus than males (8.0%) (4.9%). Type A (52.9%) was the most common according to Pell and Gregory's classification, although vertical angulations of the maxillary third molar were seen more frequently (85.32%). Congenitally missing maxillary third molars are more common in females, and position A was the most common among the maxillary third molars on a vertical level.